2021
DOI: 10.3390/md19040195
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HBV Activities of Polysaccharides from Thais clavigera (Küster) by In Vitro and In Vivo Study

Abstract: Hepatitis B virus (HBV) infection remains a major global health problem. It is therefore imperative to develop drugs for anti-hepatitis B with high-efficiency and low toxicity. Attracted by the observations and evidence that the symptoms of some patients from the Southern Fujian, China, suffering from hepatitis B were alleviated after daily eating an edible marine mollusk, Thais clavigera (Küster 1860) (TCK). Water-soluble polysaccharide from TCK (TCKP1) was isolated and characterized. The anti-HBV activity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Crude polysaccharides from seaweed and abalone viscera have antiviral activity against SARS-CoV-2 [45]. Polysaccharides from Thais clavigera (Küster) show significant anti-hepatitis B virus activity by enhancing immune cell function [46]. Isatis indigotica polysaccharide effectively inhibits the expression of IP-10, IL-6, MIG, and CCL-5 induced by human influenza virus (PR8/H1N1) and avian influenza virus (H9N2) [47].…”
Section: Discussionmentioning
confidence: 99%
“…Crude polysaccharides from seaweed and abalone viscera have antiviral activity against SARS-CoV-2 [45]. Polysaccharides from Thais clavigera (Küster) show significant anti-hepatitis B virus activity by enhancing immune cell function [46]. Isatis indigotica polysaccharide effectively inhibits the expression of IP-10, IL-6, MIG, and CCL-5 induced by human influenza virus (PR8/H1N1) and avian influenza virus (H9N2) [47].…”
Section: Discussionmentioning
confidence: 99%
“…Woo et al isolated polysaccharides from Korean edible clams with virus-cell fusion inhibitory activity against HIV infection [88]. In 2021, Fei Tang et al reported significant anti-hepatitis B virus activity with low toxicity, associated with the polysaccharides from Thais clavigera [133].…”
Section: Antiviral Activities Of Polysaccharides That Have Animal Ori...mentioning
confidence: 99%
“…In addition, their high yields, low production costs, broad-spectrum antiviral activities, and unique antiviral mechanisms suggest that sulfated polysaccharides from seaweeds are promising antiviral drugs. It should be noted that the source of marine polysaccharides is not limited to seaweed but also includes a large number of marine animals and marine microorganisms, such as Thais clavigera [ 135 ], Sepia pharaonis [ 136 ], sea cucumbers [ 137 ], Haliotis discus hannai [ 138 ], and Celtodoryxgirardae [ 139 ].…”
Section: Conclusion and Future Outlooksmentioning
confidence: 99%